Research on a cooperative spectrum sensing algorithm based on energy-constraint - Jian SU; Guo-qin NING; Feng QING (Tongxin xuebao)
With the aim of the realization of green energy-efficient cognitive communications,the energy consumption was mainly analyzed in the process of cooperative sensing and transmission,and an energy-efficient centralized cooperative spectrum sensing scheme was proposed.The spectrum sensing model of maximizing the detection lifetime of cognitive radio system was established and specified in detail.Furthermore,a searching method was presented to obtain the optimal detection lifetime and corresponding parameters.Simulation results reveal that the proposed scheme is able to extend detection lifetime and improve the probability of performing cooperative sensing for CR users with low SNR.